(untitled) (European Journal of Interdisciplinary Research and Development, 2023)
The integration course is one of the educational subjects, which is studied to deepen and increase interdisciplinary knowledge (integrative knowledge), and to form it. It is created on the basis of various types, methods, styles, objects of interdisciplinary integration.